Republic of Moldova : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criterion; Staff Report; Staff Supplement; and Press Release. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper examines the Republic of Moldova's Fourth Review under the Poverty Reduction and Growth Facility and request for Waiver of Nonobservance of Performance Criterion. Investors have been attracted by Moldova's low costs, and export prospects have improved with the resumption of wine exports to Russia and a new trade agreement with the European Union. Inflation is the main concern. While rising inflation partly reflects regional trends in food and energy prices, strong demand has been adding to inflation pressures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet